La part oubliée de l’étude des pharmacopées traditionnelles africaines - Claudie Haxaire (Revue d'ethnoécologie)
In French-speaking Africa, the pioneers of the study of “traditional pharmacopoeias” were essentially military pharmacists, such as Joseph Kerharo in Senegal, Pierre Boiteau in Madagascar, Armand Bouquet in the Côte d'Ivoire or in the Congo, in connection with the laboratory founded by Portères. They explicitly intended to lay the foundations of an ethno-pharmacology rather than only the ethnobotanical part, because it focused on the preparation and administration of the pharmakon to treat disorders, “diseases”, and note solely on the plant raw materials. But the biological (etic) orientation has prevailed. These works say very little from the point of view of practitioners and patients (emic), which is the purpose of the study of health anthropology. A reversal of perspective such as the one operated by Marc Augé (1986) concerning the anthropology of illness has been attempted, proposing an anthropology of the remedy. It is a matter of going beyond the thoroughly discussed aporias by Tim Ingold (1992-2013) between cultural ecology and ecological anthropology, to attempt the alternative ecological anthropology he proposes, and working on the medicinal (pharmacological) properties of items as so many affordances selected in a given environment by a community of humans beings or animals. This article thus follows my own path from pharmacy to anthropology, and points out the deadlocks I have encountered.